KESIAPSIAGAAN SISWA SEKOLAH DASAR DALAM MENGHADAPI BENCANA GEMPA BUMI DAN TSUNAMI DI KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - veni Nopriyanti; Helfia Edial (JURNAL BUANA, 2019)
Abstract The purpose of this study was to determine the preparedness of elementary school students in dealing with the earthquake and tsunami in the Bungus Teluk Kabung Subdistrict, Padang City. This type of research is descriptive with quantitative methods. The research sample consisted of school samples and respondent samples. The school sample was selected using the Purposive Sampling technique so 8 elementary schools were selected. The respondent sample consisted of the main sample of students and the additional sample of principals and teachers. The research data were obtained through questionnaire distribution techniques to principals, teachers and students. The results of the study showed that students of SDN 03 Batung and SDN 12 Pasar Teluk Kabung were included in the category of prepared to face the earthquake and tsunami disasters compared to SDN 19 Pasar Laban students, SDN 21 Cindakir, SDN 06 Cindakir, SDN 18 Kandang Labuhan Tarok and SDN 13 Sungai Pisang and SDN 01 Pasar Laban which are included in the category of almost ready to face the earthquake and tsunami in the District of Bungus Teluk Kabung, Padang City. Keywords: Preparedness. Earthquake and Tsunami